Simulation studies of GEM-based neutron detectors - Santos, Renan Felix dos (2023)
Neutron detectors are important in many areas such as physics, chemistry, biology, and medicine. The 3He is widely used in neutron gaseous detectors however since the early 2000s a severe shortage in the supply of this gas motivated the scientific community to search for alternative solutions with 3He-free detectors, employing 113Cd, 157Gd, 10B, or 6Li as neutron converter. A very promising structure is the Gas Electron Multiplier (GEM) combined with a boron-10 converter layer. It belongs to the family of Micro-Pattern Gaseous Detectors (MPGD) which are a type of gaseous detector with small structures that emerged in the 90s. These small structures are widely used in particle tracking systems, such as the Time Projection Chamber of the ALICE experiment in the LHC-CERN, and are proposed for many other applications, including neutron detection. The study and performance of the detectors can be developed through Monte Carlo simulations exploiting the detector response in various conditions, with different particles and configurations without the cost of building a prototype. It is common two use the frameworks GEANT4 and Garfield++ to accomplish these simulations, which comprehend the nuclear interaction of neutrons as well as the propagation of the reaction products and ionization electrons in the gas medium, its interactions, and the avalanche formation. The reaction products from 10B(n,)7Li have a high ionizing power leading to very time consuming CPU calculations making it impossible to perform them even in a computer cluster. The reduction in processing time by several orders of magnitude is crucial for a substantial study with enough statistics. Therefore, a parameterized fast simulator was developed in this work to evaluate the charge distribution in a more efficient way. This work consists in the study of the performance and optimization of thermal neutron detectors based on GEMs using simulations. The optimizations focus on improving the spatial resolution by exploiting the properties of the working gas, such as its composition and its pressure, making changes in reaction products path length and electron drift and diffusion. The results of this work indicate possible ways to optimize these detectors in addition to providing a versatile tool for future studies of this type of detector.